2017
DOI: 10.1016/j.biopsych.2015.11.020
|View full text |Cite|
|
Sign up to set email alerts
|

Ventral and Dorsal Striatum Networks in Obesity: Link to Food Craving and Weight Gain

Abstract: Obesity is linked to alterations in the functional connectivity of dorsal striatal networks relevant to food craving and weight gain. These neural alterations are associated with habit learning and thus compatible with the food addiction model of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
69
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(81 citation statements)
references
References 56 publications
(71 reference statements)
11
69
1
Order By: Relevance
“…Although we have successfully eliminated genetic confounding, the cross sectional nature of our study does not allow us to determine whether lower functional connectivity of the putamen, and its associated increased fat intake, is causal to obesity development or, rather, results as a consequence of it. Support for a causal effect of altered connectivity on obesity comes from a previous resting state study which showed that altered functional connectivity between the dorsal striatum and the somatosensory cortex predicted future weight gain [Contreras‐Rodriguez et al, ]. In the context of these findings, the altered functional connectivity of the putamen observed in our study may be explained as a vulnerability factor that might lead to weight gain, possibly through mediating effects of an acquired increased preference for high fat foods.…”
Section: Discussionsupporting
confidence: 72%
“…Although we have successfully eliminated genetic confounding, the cross sectional nature of our study does not allow us to determine whether lower functional connectivity of the putamen, and its associated increased fat intake, is causal to obesity development or, rather, results as a consequence of it. Support for a causal effect of altered connectivity on obesity comes from a previous resting state study which showed that altered functional connectivity between the dorsal striatum and the somatosensory cortex predicted future weight gain [Contreras‐Rodriguez et al, ]. In the context of these findings, the altered functional connectivity of the putamen observed in our study may be explained as a vulnerability factor that might lead to weight gain, possibly through mediating effects of an acquired increased preference for high fat foods.…”
Section: Discussionsupporting
confidence: 72%
“…In this vein, human functional magnetic resonance imaging (fMRI) studies have shown that striatal activity in response to food cues predicts chocolate intake (Lawrence et al, 2012) and weight gain after a follow-up period varying between 6 months and 3 years (Stice et al, 2008;Demos et al, 2012;Geha et al, 2013) but see (Stice & Yokum, 2018). Functional connectivity between the dorsal striatum and somatosensory cortex has also been associated with food cravings in situ and it seems to predict prospective changes in BMI (Contreras-Rodr ıguez et al, 2017).…”
Section: Reward Sensitivitymentioning
confidence: 99%
“…A resting-state fMRI study showed increased functional connectivity between striatal reward network regions and self-referential default mode network regions (medial prefrontal cortex, posterior cingulate cortex, and angular gyrus), insula, and somatosensory cortex in overweight subjects (BMI > 25) relative to healthy controls. In addition, food-craving scores were positively correlated with the increased functional connectivity in the dorsal striatum (Contreras-Rodriguez, Martin-Perez, Vilar-Lopez, & Verdejo-Garcia, 2015). As suggested by the authors, the presence of increased connectivity in the dorsal striatal network observed in obese, but not normal weight subjects, provide evidence for neural adaptations in brain reward circuitry that may contribute to addictive eating.…”
Section: Factors That Lead To the Formation Of Famentioning
confidence: 99%